2016
DOI: 10.1104/pp.16.00523
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gene Duplication in Plants

Abstract: Ancient duplication events and a high rate of retention of extant pairs of duplicate genes have contributed to an abundance of duplicate genes in plant genomes. These duplicates have contributed to the evolution of novel functions, such as the production of floral structures, induction of disease resistance, and adaptation to stress. Additionally, recent whole-genome duplications that have occurred in the lineages of several domesticated crop species, including wheat (Triticum aestivum), cotton (Gossypium hirs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
954
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,172 publications
(1,066 citation statements)
references
References 283 publications
(330 reference statements)
24
954
2
2
Order By: Relevance
“…Detection of positive selection within the B56 domain in these subclades is more consistent with neofunctionalization, escape from adaptive conflict, or subfunctionalization models for postpolyploidy retention of paralogs, rather than strict dosage balance or paralog interference models (Conant et al, 2014;Panchy et al, 2016). Preferential expansion via paleopolyploidy also could be due to coevolution of regulator/target gene pairs following polyploidization.…”
Section: B56 Isoform Specializationmentioning
confidence: 90%
See 2 more Smart Citations
“…Detection of positive selection within the B56 domain in these subclades is more consistent with neofunctionalization, escape from adaptive conflict, or subfunctionalization models for postpolyploidy retention of paralogs, rather than strict dosage balance or paralog interference models (Conant et al, 2014;Panchy et al, 2016). Preferential expansion via paleopolyploidy also could be due to coevolution of regulator/target gene pairs following polyploidization.…”
Section: B56 Isoform Specializationmentioning
confidence: 90%
“…This model proposes that genes encoding products that are constrained by specific actor-substrate interactions are retained preferentially to avoid haploinsufficiency. Duplicated genes that are initially retained to maintain gene dosage may be allowed to undergo subsequent divergence (for review, see Conant et al, 2014;Panchy et al, 2016). Gene duplications also provide mutational and regulatory robustness, or tolerance of innovations in protein sequences and expression patterns (Keane et al, 2014).…”
Section: Retention Of Duplicated Pp2a Subunit Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…This question has been addressed frequently in recent years. It has been proposed that adaptation to novel or stressful environments is correlated with the retention of duplicated genes (Flagel and Wendel, 2009;Jiao et al, 2011;Kondrashov, 2012;Panchy et al, 2016). Among the many models for duplicated gene evolution (Conant and Wolfe, 2008;Innan and Kondrashov, 2010), it is suggested that genes that should be rapidly or constantly produced in response to environmental stress might be more prone to selection after duplication (Kondrashov, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Gene and genome duplication plays a fundamental role in evolution by providing the genetic material by which new traits can arise (Conant et al, 2014;Panchy et al, 2016). Thus, comparative analysis of synteny is a powerful approach to understand the evolutionary trajectory of genes and genomes and ultimately of traits and organisms (Lee et al, 2013;Jiao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%